Review—Progress in High Performance III-Nitride Micro-Light-Emitting Diodes. (7th November 2019) - Wong, Matthew S.; Nakamura, Shuji; DenBaars, Steven P.
Abstract : The developments of high performance InGaN based micro-light-emitting diodes (μLEDs) are discussed. We first review the early demonstrations of μLEDs and the state-of-the-art outstanding achievements on the emerging high-quality display and visible-light communication applications. Due to the miniature dimensions of μLEDs, the key understandings and the significant device advancements to achieve excellent energy efficiency are addressed. Lastly, two other critical challenges of μLEDs, namely full-color scheme and mass transfer technique, and their potential solutions are explored for future investigations.